Philosophy of Art Criticism Between Theory and Practice (Al-Academy, 2026)
Some philosophical theories Provides us a new scientific visions in the contemporary of art criticism Philosophy. These visions showing a more precise understanding of uncovering truths and analyzing the structures of artworks in a more professional and accurate manner than traditional critical approaches. To avoid confusion between the essence of art criticism and the philosophy of art criticism, we have developed this comprehensive study, bridging the gap between theoretical and practical applications within the academic learning process. It aims to understand art criticism according to both classical methods and modern art criticism, and to examine the differences between these two approaches in the visual arts in general. It is also worth noting that art criticism is currently the dominant approach in art circles and academic curricula across most specialized educational institutions. This approach may appears traditional to describe and analysis of artworks, limited to either impressionistic or contextual methods. The latter approach focuses on the artist's biography and social and emotional life, while the former considers the artwork as a matter with fundamental compositional principles, or the latter is a simplified historical method. Criticism in this way deals with the artwork and the artist equally, and they can't be separated. Even if the modern constructivist method considers the artwork to be self-generated and excludes the role of the artist in it, it is ultimately related to scientific judgment as a fundamental result, not a definitive one, in the critical process as a whole.